2006
DOI: 10.1029/2006gl028440
|View full text |Cite
|
Sign up to set email alerts
|

On the variability of the shape‐slope parameter relations of the gamma raindrop size distribution model

Abstract: [1] The gamma parameters have been derived on the ground with the disdrometer and aloft with VHF and UHF radar measurements made at Gadanki in the southwest monsoon season. They have been used to study the variability of the shape-slope (m -L) relation with the climatic regime and also as a function of height. The m -L relation obtained at Gadanki differs from that derived at Florida and Oklahoma indicating climatic differences in the relation, which could be due to the microphysical differences in the rain DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 20 publications
1
56
0
Order By: Relevance
“…The system description of the LAWP is given in Rao et al (2001). Important specifications of the LAWP can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The system description of the LAWP is given in Rao et al (2001). Important specifications of the LAWP can be found in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the rain categories, the coefficients of the µ-Λ relations with 95% confidence bounds and Pearson correlation coefficients. The different rain categorizations, i.e., R ≥ 5 mm/hr & drops ≥ 1000 used by Brandes et al [5], z ≥ 30 dBZ & drops ≥ 500 used by Narayana et al [12], and R ≥ 1 mm/hr used by Brawn and Upton [13], are also included in the table for comparison with other published results. As can be seen in Table 1, for the rain categories for which there are more lower rain rates included, such as R < 2 mm/hr and R ≥ 1 mm/hr, the coefficient 'C' of the polynomial fit is not only negative, but very small, with values of −0.004 and −0.005 respectively.…”
Section: µ-λ Relationshipmentioning
confidence: 99%
“…He concluded that the equivalence between the µ-Λ relation and Testud's function indicates the physical information in the µ-Λ relation of the constrained-gamma (C-G) model proposed by [2]. Narayana et al [12] studied the variability of the µ-Λ relation using the Joss-Waldvogel distrometer (JWD) data measured at Gadanki, India, under the conditions, reflectivity ≥ 30 dBZ and number of drops ≥ 500. They used 3rd, 4th and 6th moments to fit the gamma model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have not been many measurements in India. Some Verma and Jha (1996), Reddy and Kozu (2003), Sasi Kumar et al (2003), Mali et al (2003), Krishna Reddy et al (2005), Roy et al (2005), Rao et al (2006) and . We present here the measurement and derivation of a rain DSD model for 4 different locations in southern India, viz.…”
Section: Introductionmentioning
confidence: 99%